DIETARY PREBIOTICS IN AUGMENTING THE ANTIOXIDANT ENZYMES AND THY ROID HORMONES IN SVVU T17 CROSSBRED PIGS (Indian Journal of Animal Production and Management, 2025)
The present study was conducted to investigate the effect of supplementation of  prebiotics mannan-oligosaccharide (MOS) on antioxidant and thyroid status in  SVVU T17 crossbred pigs. Twenty-four SVVU T17 crossbred male grower pigs  above 2 months of age were randomly divided into four groups with six piglets in  each group i.e., P0, P1, P2 and P3 groups. The experiment was conducted for 45  days and at the end of experiment blood samples were collected for estimation of  antioxidants and thyroid levels. There was a significant increase (P
Keywords: Antioxidant enzymes; Mannan-oligosaccharide; MDA; SVVU T17 pig